Triple Local Recurrence of Synovial Sarcoma: A Case Report - Edward, Mouli; Akbar, Kukuh Ali ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2023)
Background: Synovial Sarcoma (SS) hardly appears on non-extremity sites (20% of cases). Even rarer is a local recurrence, which occurs between 10-30% of cases. Here, we present a rare case of hip Synovial Sarcoma, which recurs three times.Case Report: A 33-year-old male came to our outpatient clinic with chief complaints of a sudden ingrowing mass on his left hip. The lump is the size of a chicken egg and doesn't get bigger over time. There was palpable tenderness felt whenever he touched the lump. The patient was diagnosed with SS of the left hip with IIB stage from additional radiographic and histopathologic examination. Surgical-wide resection had been done three years before the visit, and chemotherapy six times. The lump reappeared one year before the visit, and the patient underwent a second surgery. The mass re-surfaced within the same region on the current visit for the third time, and he underwent the same surgical treatment afterward. Two years after the third surgery and adjuvant chemotherapy, the patient had no complaint about a lump and planned a radiograph evaluation.Discussion: Detailed examination from history taking, physical examination, histopathologic, and radiological results is important to determine appropriate staging. With proper staging, physicians can better understand disease prognosis and risk of recurrence or metastases.Conclusions: The third recurrence may still happen on SS. Its unique location might contribute to this unique occurrence, and the size of the tumor makes the recurrence rate higher.